PENGARUH PERSEPSI KEPUASAN TERHADAP LOYALITAS KONSUMEN (Studi Kasus Rumah Potong Ayam PT. Ciomas Adisatwa, Tbk.) - Khairil Anwar (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aims to find out is there any influence between the variables of customer satisfaction with RPA Consumer Loyalty PT. Ciomas. This study was carried out to customers RPA PT Ciomas which has transact more than one year. This study is a qualitative research method and an explanatory research design (explanatory research). Total sample of 37 customers RPA PT. Ciomas. Data were analyzed using univariate and bivariate analysis. The results showed there was a significant relationship between the variables of customer satisfaction (p <0.01), and customer loyalty RPA PT. Ciomas.